2005
DOI: 10.1152/ajpheart.00083.2004
|View full text |Cite
|
Sign up to set email alerts
|

The α2-isoform of Na-K-ATPase mediates ouabain-induced hypertension in mice and increased vascular contractility in vitro

Abstract: . The ␣ 2-isoform of Na-K-ATPase mediates ouabain-induced hypertension in mice and increased vascular contractility in vitro. Am J Physiol Heart Circ Physiol 288: H477-H485, 2005. First published September 30, 2004 doi:10.1152/ajpheart.00083.2004.-Although ouabain is known to induce hypertension, the mechanism of how this cardiac glycoside affects blood pressure is uncertain. The present study demonstrates that the ␣2-isoform of the Na-K-ATPase mediates the pressor effects of ouabain in mice. To accomplish th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
169
3
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(194 citation statements)
references
References 38 publications
18
169
3
4
Order By: Relevance
“…Elevated EO levels were also observed in rodents with DOCA-salt hypertension (41,43), ACTH-hypertension (20, 20a, 115), reduced renal mass hypertension (108), and in salt-sensitive Milan strain rats on a high-salt diet (22,23). Indeed, a critical corollary to these reports is the evidence that prolonged administration of ouabain, itself (a Strophanthus steroid), but not digoxin or digitoxin (Digitalis steroids), elevates BP in normal rats and mice (19,60,72,74,75,116).…”
Section: Endogenous Ouabain and Other Endogenous Cardiotonic Steroidsmentioning
confidence: 96%
See 1 more Smart Citation
“…Elevated EO levels were also observed in rodents with DOCA-salt hypertension (41,43), ACTH-hypertension (20, 20a, 115), reduced renal mass hypertension (108), and in salt-sensitive Milan strain rats on a high-salt diet (22,23). Indeed, a critical corollary to these reports is the evidence that prolonged administration of ouabain, itself (a Strophanthus steroid), but not digoxin or digitoxin (Digitalis steroids), elevates BP in normal rats and mice (19,60,72,74,75,116).…”
Section: Endogenous Ouabain and Other Endogenous Cardiotonic Steroidsmentioning
confidence: 96%
“…In related studies, Lingrel and colleagues have shown that transgenic mice with a mutated ␣ 2 Na ϩ pump that renders this isoform resistant to ouabain are resistant to both ouabaininduced hypertension (19) and ACTH-induced hypertension (20, 20a). Moreover, the plasma from mice with ACTHinduced hypertension had significantly elevated levels of a water-soluble substance that cross-reacted with antidigoxinspecific Fab fragments (Digibind) (20).…”
Section: How Does Low-dose Ouabain Augment Contractility?mentioning
confidence: 99%
“…The α3 subunit was originally indicated to be present in the membrane in the vicinity of Ca 2+ store sites in blood smooth muscle cells [6,26] but a recent knockout experiment suggests the presence of the α2 in such a membrane domain of smooth muscle cells [27]. As a result, the α2 subunit localized in the plasma membrane closely associated with Ca 2+ store sites may be α2 irrespective of the cell type.…”
Section: Functions Of Na + K + -Atpase Isozymesmentioning
confidence: 99%
“…Tail-cuff measurements were obtained by using a Visitech (Apex, NC) system computerized apparatus, as described in ref. 32. In brief, for each measurement, 10 preliminary blood pressure measurements were obtained to acclimate the mice to the apparatus, and these were followed by 10 recorded SBP and heart rate measurements.…”
mentioning
confidence: 99%